Development and validation of a picture storybook based on local wisdom to strengthen 'gotong royong' and critical thinking among elementary students - Devi Fitriasti; Wuri Wuryandani (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to: 1) produce a picture storybook based on local wisdom that is feasible for strengthening the character of 'gotong royong' and critical thinking skills, 2) test the effectiveness of the picture storybook based on local wisdom in strengthening the character of 'gotong royong' and critical thinking skills, and 3) test the practicality of the picture storybook based on local wisdom for strengthening the character of 'gotong royong' and critical thinking skills. This research uses the Borg & Gall research method, which consists of 10 steps: (1) preliminary research and information collection, (2) planning, (3) product development, (4) preliminary field testing, (5) main product revision, (6) main field testing, (7) operational product revision, (8) operational field testing, (9) final product revision, and (10) dissemination and implementation. The results of the study show that: 1) the developed picture storybook based on local wisdom is feasible to be used for strengthening the character of 'gotong royong' and critical thinking skills, 2) the developed picture storybook based on local wisdom is effective in strengthening the character of 'gotong royong' and critical thinking skills. Validation instrument by experts judgment. The results of the operational test showed a significance level of 0.00 < 0.05, indicating a significant difference in the strengthening of 'gotong royong' character and critical thinking skills between the experimental classes with 21 students and 23 students in control classes, 3) the developed picture storybook based on local wisdom is practical to use for strengthening students' character of 'gotong royong' and critical thinking skills based on teacher and student responses.